2011
DOI: 10.1088/1748-0221/6/01/c01067
|View full text |Cite
|
Sign up to set email alerts
|

2D-sensitive hpxe gas proportional scintillation counter concept for nuclear medical imaging purposes

Abstract: The operation and first images of a high pressure xenon Gas Proportional Scintillation Counter (GPSC) are presented. In this setup, primary electrons produced by the absorption of Xor γ-rays in the gas medium drift to a region where the electric field is set to a value above the gas scintillation threshold, the scintillation region. The primary ionization signal is amplified through the electroluminescence produced along the electron drift in this region. A Micro-Hole and Strip Plate covered with CsI (CsI-MHSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although several different configurations have been investigated (Bolozdynya et al ., 1997; Tsyganov et al ., 2008; Azevedo et al ., 2011), gas-based detectors have not found widespread use in SPECT and will not be discussed further.…”
Section: Spect Detector Basicsmentioning
confidence: 99%
“…Although several different configurations have been investigated (Bolozdynya et al ., 1997; Tsyganov et al ., 2008; Azevedo et al ., 2011), gas-based detectors have not found widespread use in SPECT and will not be discussed further.…”
Section: Spect Detector Basicsmentioning
confidence: 99%
“…The wide range of applications that rely on the most advanced EL detectors include doublephase liquid noble gas time projection chamber (TPC) for rare event searches (e.g. dark matter [8,[13][14][15][16][17], neutrino physics [18][19][20][21], low energy X-rays [22,23], and nuclear medical imaging [24]). New technologies such as linear (APD) or Geiger (SiPM) Avalanche Photo-Diode [25], hybrid devices [26] and fast Charge-Couple Device CCD [27], are extremely sensitive and allow EL-based readout to deliver better signal-to-noise ratio and better energy resolution compared to the traditional charge-based detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental measurements have shown that the increase of gas pressure leads to an improving of the position resolution [2,7,8], however the measurement technique relies on detectors where the position resolution measured depends on the detector gain and on the electron diffusion in the gas. Thus, in order to decouple the position resolution from the detector gain, the intrinsic position resolution of pressurized pure noble gases (Ar and Xenon, in the pressures range 1-10 bar) was calculated, studied and compared with the available experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The most usual way to overcome this problem is to increase the gas pressure, thus increasing the number of gas atoms/molecules per unit volume. Also, the pressure increase will enhance the energy resolution and light production when, for instance, coupled to an electroluminescence-based readout [2][3][4]. It is expected that the pressure increase will reduce the electrons diffusion in the gas medium, which will in turn result in a better position resolution when compared to the value obtained at atmospheric pressure [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation